Realta. - Wong, See Hua. (2012)
Realta is a collaboration project between two students from two majors, namely Geraldine Ghwee from Interactive Media and Wong See Hua from Visual Communication. The end result is a tablet based Flash game that explores the relationship between game mechanics and story within the game, integrating in-game characters with mechanics while